The Burden of Love: Moravian Conversions and Emotions in Eighteenth‐Century Labrador. (22nd May 2015) - Van Gent, Jacqueline
Abstract : The Moravian Church was a highly successful Protestant mission society which developed very specific emotional registers to create an imagined community across very diverse cultures. This article discusses the social regulation of emotions and the indigenous responses to a Moravian emotional style as part of the conversion process on Moravian missions in the eighteenth century. One of the core elements of Moravian spiritual conversion and identity was the love of Christ and his spiritual sufferings which was expected to be displayed in specific ways by converts. Moravian understandings of Christ's love and conversion included a strong somatic component, spiritual states were expressed in attributes and states of the heart, such as a "warm" or a "cold" heart. Tears, which were believed to flow from the heart, are another indicator of spiritual condition and linked to conversion. The historical meaning of this Moravian love was, however, far from being non‐ambiguous. A closer reading of the expressions of indigenous converts suggest that emotions associated with conversions, such as love, constituted a complex set of social meanings which reflected the colonial hierarchies, violence, and social power differences in which Moravian conversions took place.